Motor Skill Learning Strategy for School-Aged Children with Autism Spectrum Disorders: A Systematic Literature Review - Kusumastuti, Dewi Ekasari; Wahab, Rochmat (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
Strategies and their efficacy in supporting children with ASD to learn motor skills have not been widely discussed. Therefore, little information is available on this subject. This systematic review was designed to describe motor skills learning strategies for children with school-age ASD. The method used in this research is the PRISMA method. Articles were retrieved from two databases, namely Scopus and Web of Science. The articles were collected from 2010 to 2025, and 17 articles met the inclusion and exclusion criteria. The results of this study indicate that (1) there are nine types of strategies used in learning motor skills of children with school-age ASD, namely: implicit learning; attention-focused instruction; game-based learning; observational learning; real-time visual feedback; virtual-real environment learning transfer; task modification; TMGD-2 program; CPRT; (2) all nine types of strategies proved to be effective; (3) while recommendations for future research focus on the development of learning strategies based on the ability levels of children with ASD and longitudinal evaluations, there are pressing challenges in implementation. Collaboration between educators and therapists is essential to the strategy's effectiveness.